Plasma ammonia response to sprint swimming - Ring, S.; Mader, A.; Mougios, V. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: To study the plasma ammonia response after sprint crawl swimming. METHODS: Nine sprinters (S) and ten non-sprinters (NS) completed a 15-, a 25- and a 50-m crawl at maximal intensity with a 10-min and a 15-min resting period in-between. Capillary blood samples were collected before and at regular intervals after each effort for plasma ammonia determination. RESULTS: Ammonia kinetics differed among distances, but not between groups, with peak values (observed 2-8 min postexercise) being higher after 50 m as compared to shorter distances. Significant differences between S and NS were found in peak ammonia after 50 m (124.5 +/- 58.2 vs 98.7 +/- 6.3 mumoL-1) and in the change of ammonia relative to swim time (delta NH3/delta t) after 25 m (2.66 +/- 1.87 vs 1.49 +/- 0.84 mumol L-1 s-1) and 50 m (1.87 +/- 1.33 vs 1.01 +/- 0.49 mumol L-1 s-1). delta NH3/delta t was highest after 15 m (3.33 +/- 2.53 in S, 3.92 +/- 1.67 mumol L-1 s-1 in NS). CONCLUSIONS: These differences in the plasma ammonia response to sprint swimming according to duration and athlete seem to be connected to distinctions in muscle fiber profile and energy providing processes.